Progress and key technology analysis of bronchoscopic robot - Xingguang DUAN; Dongsheng XIE; Fengxinyun FANG; Rui HE; Changsheng LI (工程科学学报)
In recent years, bronchoscopic robot technology has emerged as a groundbreaking advancement in medical technology, particularly in the diagnosis and treatment of lung diseases. Although traditional bronchoscopy is effective, it is associated with significant challenges in achieving the level of precision required for accurately detecting and treating lung tissue and lesions. Although navigation-guided bronchoscopy has made notable strides in addressing some of these limitations, further improvements are necessary to enhance its precision, accessibility, and overall effectiveness. Bronchoscopic robot technology bridges this gap by integrating robotics and advanced imaging sensors to improve diagnostic and therapeutic capabilities. The core of bronchoscopic robot technology lies in its ability to combine robotic arm dexterity with the clarity provided by state-of-the-art imaging systems. This synergy allows for highly precise detection and treatment of lung tissue and lesions. The inherent flexibility of robotic arms enables physicians to navigate complex bronchial networks with ease, facilitating accurate lesion localization, performing delicate biopsies, and conducting minimally invasive surgical procedures. These capabilities represent a significant leap forward in treating lung diseases, providing clinicians with tools that surpass the limitations of conventional bronchoscopy in terms of precision and control. This paper provides a comprehensive overview of the current development status and the key technologies underpinning bronchoscopic robot technology. The first step is to analyze the application of this technology in clinical diagnosis and treatment. This review examines the use of bronchoscopic robots in medical settings and evaluates their impact on procedural accuracy and efficiency. By highlighting real-world applications, this paper emphasizes the transformative role that this technology plays in improving lung disease outcomes. The second focus of this paper delves into the technical principles that form the foundation of bronchoscopic robot technology. This section explores critical aspects, such as mechanism design, navigation methods, and control systems. A detailed understanding of these technical components not only provides insights into how the technology operates but also identifies potential areas for future refinement. For instance, advanced navigation techniques enable accurate tracking of instruments within the lung’s intricate structure, whereas innovative control systems ensure smooth, precise operation of robotic components. Furthermore, this paper discusses the current industrialization status of bronchoscopic robots, evaluating the progress made in translating laboratory innovations into practical clinical tools. This includes an assessment of the technology’s readiness for widespread adoption, challenges in scaling production, and efforts to integrate it into routine medical practices. Understanding the industrial landscape is essential for gauging the potential for widespread clinical use and its long-term impact on healthcare. Finally, this paper looks toward the future by exploring research directions and emerging development trends. One major trend is the integration of lesion navigation, biopsy, real-time confirmation, and immediate treatment into a unified bronchoscopic diagnosis and treatment platform. In addition, combining artificial intelligence (AI) with robotic systems is anticipated to significantly enhance the intelligence of bronchoscopic robots. AI-driven algorithms can provide advanced decision-making support, improve diagnostic accuracy and enable personalized treatment strategies. These advancements have the potential to revolutionize the field by making procedures less invasive and more effective. By summarizing the current development status and key technologies of bronchoscopic robot technology, this paper highlights its immense potential to transform the diagnosis and treatment of lung diseases. The integration of robotics, imaging, and artificial intelligence is paving the way for more accurate, efficient, and patient-friendly medical procedures. As this technology continues to evolve, it promises to deliver improved patient outcomes, reduce procedural risks, and redefine the standards of care in pulmonary medicine.